2021
DOI: 10.1097/md.0000000000028127
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple method for measuring tedizolid concentration in human serum using HPLC with a fluorescent detector

Abstract: The objective of the present study was to develop a method to measure tedizolid (TZD) concentration for studying target concentration intervention, pharmacokinetics, and pharmacodynamics of TZD. We established a high-performance liquid chromatography-fluorescence detector assay to measure the TZD concentration in serum for clinical application. Chromatographic separation was carried out on a 5 μm octadecyl silane hypersil column 150 mm × 4.6 mm. The mobile phase consisted of 0.1 M phosphoric acid and methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For tedizolid, the mean (range) tedizolid saliva-to-unbound serum concentration ratio was 0.39 (0.07-0.74), suggesting lower passage into the saliva than linezolid. As in previous studies (29,32), the serum protein-binding rates were different between linezolid and tedizolid in the present study. The median (IQR) serum protein-binding rates are 18.2 (15.8-19.8) in linezolid and 60.3 (48.0-71.1) in tedizolid, respectively (Table 1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For tedizolid, the mean (range) tedizolid saliva-to-unbound serum concentration ratio was 0.39 (0.07-0.74), suggesting lower passage into the saliva than linezolid. As in previous studies (29,32), the serum protein-binding rates were different between linezolid and tedizolid in the present study. The median (IQR) serum protein-binding rates are 18.2 (15.8-19.8) in linezolid and 60.3 (48.0-71.1) in tedizolid, respectively (Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…Total and unbound serum concentrations of linezolid and tedizolid were measured using the improved methodology based on our previously published high-performance liquid chromatography (HPLC) methods (30, 32). Saliva samples were applied in the same manner as serum to measure saliva concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Validated, simple, or enantio-separation of tedizolid using high-performance liquid chromatography has been proposed with tandem mass spectrometry, ultraviolet, or fluorescence detection [ 12 , 13 ]. Relatively good penetration of tedizolid into the interstitial fluid of adipose and muscle tissues has been demonstrated in healthy volunteers [ 9 ], whereas inadequate plasma-to-cerebrospinal fluid ratios of 54% have been reported for tedizolid [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid and plasma levels of tedizolid were measured using a reversed-phase, high-performance, liquid chromatography system (Shimadzu, Kyoto, Japan) with a Mightysil RP-18GP Aqua column (5 μm, 150 × 4.6 mm, Kanto Chemical, Tokyo, Japan) equilibrated in a mobile phase comprising 35% CH 3 CN in 0.1% aqueous phosphoric acid at a flow rate of 1.0 mL/min and a column temperature of 45 °C. Fluorescence monitoring was carried out at excitation and emission wavelengths of 300 and 340 nm [ 12 ], respectively, and ultraviolet monitoring was done at 254 nm. The samples (10 µL) were infused using an autosampler.…”
Section: Case Presentationmentioning
confidence: 99%
“…Finally, Tsuji et al reported the quantification of serum TZD concentrations using high-performance liquid chromatography-fluorescence (HPLC-FL) [ 84 ]. High linearity with R 2 > 0.999 was exhibited over a concentration range from 0.025 to 10 μg/mL for TZD.…”
Section: Tdm Of Tedizolidmentioning
confidence: 99%